Pemahaman Wirausaha Bagi Remaja dan Ibu-Ibu Majlis Taklim Al-Muslimah Kelurahan Tembesi Kota Batam - Ibrahim, Ukas; Jamba, Padrisan; Husda, Anggun Permata (PUAN INDONESIA, 2024)
The material provided in this coaching is divided into 2 groups, namely the legal group and the business group aimed at "Teenagers/Young Generation", and Ms. Majlis Taklim Al-Muslimah, especially Majlis taklim, Rexvin Boulevad Housing, Tembesi Village, Batam City. in the legal group is to provide an introduction and/or understanding regarding the understanding of regulations relating to trade and other businesses, because after all, in the future they will be the next generation of religious, national and state leaders, especially to the younger generation. And mothers as motivators in building home businesses ladder. So that it will be better in the future, from an early age, we will be given an understanding of the legal rules that exist among the people of the nation and state, with the hope that with this kind of education, teenagers and women in the council will better understand and implement them, in their business activities and/or in the business world. Brief education and/or coaching like this can be understood, the training material given to business groups is to provide an introduction and/or understanding as well as inviting teenagers/young generations and mothers of taklim councils, especially for majlis planning in developing their business talents, to understand the importance to live independently in the future, of course, understand how to do good work, be honest and fair, and understand how development goes.